Analisis Faktor Yang Berhubungan Dengan Penerapan Surgical Safety Checklist Di Kamar Operasi Rumah Sakit Kota Batam - Endang Yuliati; Hema Malini; Sri Muharni (Jurnal Endurance, 2019)
The use of the Surgical Safety Checklist (SSC) is associated with improving patient care according to nursing process standards includes the quality of work of the operating room nurse team. The form of professionalism in the operating room is how the application of a surgical safety checklist as the standard procedure for patient safety in the operating room. This study aims to determine the relationship of characteristics, knowledge, and motivation of nurses in the application of the surgical safety checklist in the operating room of a Batam city hospital. This research is quantitative using an observational analytic research design. This study was conducted on 67 nurses who were taken by total sampling. This research was conducted in three Batam City Hospitals, with hospital accreditation at the same level. Data were analysed by univariate and bivariate using the chi-square test. The results of the study found that most nurses had education at diploma level, with a working period experiences of > 6 months (82%); good knowledge (53.7%) with low motivation (57.7%). There is a relationship between education (p = 0.042); length of work experience (p = 0.010); knowledge (p = 0.002); and motivation (p = 0.05) with the application of SSC. It is expected that health services carry out SSC following the applicable SOPs in the Hospital so that it can reduce work accident rates and improve patient safety. Penerapan Surgical Safety Checklist (SSC) berhubungan langsung dengan kualitas asuhan keperawatan yang termasuk adalah bagaimana perawat menerapkan fungsi sebagai bagian dari kamar operasi. Bentuk profesionalisme ini menjadi standar bagaimana kemampuan perawat menerapakan SSC. Tujuan penelitian adalah mengetahui hubungan karakteristik perawat, pengetahuan dan motivasi dengan penerapan SSC di kamar operasi. Penelitian ini menggunakan desain kuantitatif Cross Sectional dengan jumlah sampel 67 orang perawat kamar operasi. Data dianalisa dengan distribusi frekuensi dan uji hubungan bivariat. Didapatkan penerapan SSC perawat kota Batam masih kurang baik, dengan faktor yang mempunyai hubungan adalah Pendidikan, pelatihan dan pengetahuan. Diharapkan perawat mampu menerapkan SSC sesuai dengan Standar pelaksanaan fungsi perawat dikamar operasi.